(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
Canine parvovirus is one of the most common infectious diseases of dogs. A study was carried out to diagnose the infection of canine parvovirus in street dogs from different places of Mymensingh Town. Rectal samples were collected from January to April, 2015. A total of 114 rectal swabs were collected conveniently from street dogs of Mymensingh. The samples were diagnosed using RapiGEN Canine Parvo Virus Ag Test Kit. The association of CPV infection with demographic variables was assessed by Chisquare test. The overall prevalence of CPV was 32.0% in dogs. The prevalence of parvovirus infection was found to be significantly higher in puppies and 6 months of age (58.3%) than those >24 months of age (p=0.005). The prevalence of canine parvovirus infection also varied significantly in different study area (p=0.003). The prevalence of canine parvovirus infection was higher in male (34.4%) than that in female (30.2%) but it was not statistically significant. Res. Agric., Livest. Fish.2(3): 459-464, December 2015